Histone replacement marks the boundaries of cis-regulatory domains. - Mito, Y.; Henikoff, J.G.; Henikoff, S. (Science, 2007)
Cellular memory is maintained at homeotic genes by cis-regulatory elements whose mechanism of action is unknown. We have examined chromatin at Drosophila homeotic gene clusters by measuring, at high resolution, levels of histone replacement and nucleosome occupancy. Homeotic gene clusters display conspicuous peaks of histone replacement at boundaries of cis-regulatory domains superimposed over broad regions of low replacement. Peaks of histone replacement closely correspond to nuclease-hypersensitive sites, binding sites for Polycomb and trithorax group proteins, and sites of nucleosome depletion. Our results suggest the existence of a continuous process that disrupts nucleosomes and maintains accessibility of cis-regulatory elements.